(untitled) (Ozone Therapy Global Journal, 2016)
Vertebral pathological fractures have traditionally handled with rest, vertebroplasty or surgical fixation. In the present case the severe pain caused by the fracture compressing Medullary Cone, was controlled with neuraxial analgesia and we subsequently observed that the fracture was reduced as a result of the epidural administration of ozone